2020
DOI: 10.1515/nanoph-2020-0459
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional confinement and waveguide effect of Dyakonov surface waves in twisted confined media

Abstract: We theoretically study Dyakonov surface waveguide modes that propagate along the planar strip interfacial waveguide between two uniaxial dielectrics. We demonstrate that owing to the one-dimensional electromagnetic confinement, Dyakonov surface waveguide modes can propagate in the directions that are forbidden for the classical Dyakonov surface waves at the infinite interface. We show that this situation is similar to a waveguide effect and formulate the resonance conditions at which Dyakonov surface waveguide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
5
0
2
Order By: Relevance
“…При этом анализировались лишь некоторые частные случаи границ раздела двуосных кристаллов при относительно простых пространственных ориентациях их оптических осей. Кроме того, в литературе изучались и другие разновидности волн Дьяконова, существование которых возможно на границах раздела других типов веществ, таких, как гиперболические, хиральные и бианизотропные материалы [16][17][18][19], а также возникающих в ограниченных средах [20][21][22][23].…”
Section: Introductionunclassified
“…При этом анализировались лишь некоторые частные случаи границ раздела двуосных кристаллов при относительно простых пространственных ориентациях их оптических осей. Кроме того, в литературе изучались и другие разновидности волн Дьяконова, существование которых возможно на границах раздела других типов веществ, таких, как гиперболические, хиральные и бианизотропные материалы [16][17][18][19], а также возникающих в ограниченных средах [20][21][22][23].…”
Section: Introductionunclassified
“…Only some particular cases of biaxial crystal interfaces with relatively simple spatial orientations of their optical axes were analyzed. In addition, other varieties of Dyakonov waves, the existence of which is possible at the interfaces of other types of substances, such as hyperbolic, chiral and bianisotropic materials [16][17][18][19], as well as arising in limited media [20][21][22][23] have been studied in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, a practically important case of Dyakonov-like surface waves in finite-size resonator structures has been studied for cylindrical waveguides [34,35] as well as for flat interfacial strip waveguides [36,37]. It has been demonstrated that due to a non-zero curvature of cylindrical waveguides, Dyakonov surface waveguide modes (DSWMs) in them inevitably have radiative losses.…”
Section: Introductionmentioning
confidence: 99%